STUDIES CONCERNING THE BEHAVIOR OF THE SUSPENDED SOLIDS IN THE MIXING PROCESS (Journal of Engineering Studies and Research, 2015)
A high importance is given to the studies concerning the most reliable mixing process with a minimum of energy consumption, because the mixing process is an often used operation in various industries. The main purpose of this paper is to determine and to identify the behavior of the dispersed phase, in this case, the solid particle, during the mixing process. Through the experiment, the mixing process was recorded using a High-Speed camera, which enables following the behavior of the solid particle. The resulting data were used for different types of charts.
Keywords: solid suspensions; dispersion; the travel speed; mixing process